Analisis Desain Hidrolik IPAL Sistem Biocord dalam Mengatasi Pencemaran Air Pada Danau Duta Harapan - Maruli Nathaniel; Rizka Arbaningrum (Civil Infrastructure Engineering and Architectural Design, 2021)
Abstract: The Wastewater Treatment Plants (WTP) is an engineering structure and equipment and equipment specifically designed to process or treat process residual fluids so that the remainder of the process becomes feasible to be disposed of into the environment. Most of the WTP are permanently installed, usually, the wastewater first flows through the biological treatment stage and then ends in the retreatment stage. Duta Harapan Lake is one of the lakes in the Bekasi area, West Java. Currently, Danau Duta Harapan WTP is still redesigning it so that it is not operating optimally. This research serves to design the WTP located at Duta Harapan Lake to meet the requirements of the minister of environment regulation no. 68 of 2016, concerning the quality standards of domestic wastewater. Domestic wastewater generated by Duta Harapan housing which is assumed to contain 500 households dispose of wastewater through housing drainage to be filtered by WTP for 400 m3 / day. To manage the waste, an anaerobic-aerobic WTP is planned which consists of an initial settling basin zone, anaerobic zone, an aerobic zone, and a final settling zone or a polishing zone equipped with biocord filter media. From the WTP processing, it is estimated that the quality of domestic wastewater will be BOD: 2 mg / l, COD: 5 mg / l, and TSS: 2 mg / l.